2022
DOI: 10.1007/s00268-022-06683-x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of ICG Angiography‐Guided Thyroidectomy for Preserving Parathyroid Function

Abstract: Introduction Hypoparathyroidism is the most frequent complication after total thyroidectomy and, when permanent, it becomes a severe chronic disease. We assessed the usefulness of indocyanine green (ICG) angiography‐guided thyroidectomy to reduce the postoperative hypocalcemia. Methods Prospective study with two consecutive cohorts of patients who underwent total thyroidectomy: historical control group (CG) and angiography‐guided thyroidectomy group (AG). In all patients, ICG‐angiography was performed at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…A total of 1743 articles were screened (Figure 1) and 237 full‐text articles were assessed for eligibility. After careful selection of the articles, 66 studies were eligible for the final synthesis and were included in this review 10,14,23,24,27‐88 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 1743 articles were screened (Figure 1) and 237 full‐text articles were assessed for eligibility. After careful selection of the articles, 66 studies were eligible for the final synthesis and were included in this review 10,14,23,24,27‐88 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the ICG doses, the dose of 1 ml of ICG was arbitrarily selected as in our experience it was the minimum amount of ICG offering clear visualization of the PGS and its feeding vessels. All the remaining doses (3 ml each) were taken from the fists studies from Vidal et al ( 7 , 16 ) that were also used in all our previous published papers ( 15 , 18 ). However, final consensus regarding the ICG doses has not been published yet.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous single-center study, it was found that in a prospective cohort of patients in which ICG arteriography was performed before removal of the thyroid gland, the rate of permanent hypoparathyroidism was 0% as compared with 11.9% in a cohort of historical controls ( 14 ). Based on a more conservative approach, a rate of permanent hypoparathyroidism of 2% is estimated in the ICG angiography-guided thyroidectomy and 8% in the control group.…”
Section: Methodsmentioning
confidence: 98%
“…The rates of early and permanent hypocalcemia were significantly lower in the angiography-guided thyroidectomy group (5.6% vs. 26.2%, p = 0.011, and 0% vs. 11.9%, p =0.032, respectively) than in controls. Moreover, a significant higher rate of well vascularized parathyroids at the end of the surgery (score 2) in the angiography-guided thyroidectomy group (52.9% vs. 39.2%, p = 0.018) was also seen ( 14 ). Results obtained in this cohort study provided the rationale for the design of a randomized controlled clinical trial.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation